Impact of interstitial carbon on self-diffusion in CoCrFeMnNi high entropy alloys. (November 2020) - Lukianova, O.A.; Rao, Z.; Kulitckii, V.; Li, Z.; Wilde, G.; Divinski, S.V.
Abstract: Tracer diffusion of the matrix elements in CoCrFeNiMn-based high-entropy alloys with 0.2, 0.5 and 0.8 at.% carbon is measured at 1373 K. The diffusion coefficients are found to depend non-monotonously on the carbon content. The diffusion retardation in low-C alloys is discussed in terms of the impact of interstitially-dissolved carbon on the vacancy concentration and the migration barriers in the alloy. In high-C alloys, formation of carbides alternates the observed trends, most probably by increasing the total vacancy concentration. Graphical abstract: Image, graphical abstract